RISIKO PRODUKSI DAN KEEFISIENAN RELATIF USAHATANI BAWANG PUTIH DI KABUPATEN KARANGANYAR( PROCUDTION RISK AND RELATIVE EFFICIENCY OF GARLIC FARMING IN KARANGANYAR REGENCY) - , Sriyadi (Pembangunan Pedesaan, 2010)
The research aimed at analyzing the income risk, the farmer behavior toward risk, and the level of relative efficiency of garlic farming. This research has been done in Karanganyar Regency using multistage cluster sampling method, with the sample of 200 farmers chosen using simple random sampling method. The income risk was measured by variation coefficient. Analytical method of farmer behavior toward risk used utility function of quadratic form and analysis the level of relative efficiency used profit dynamic maximize. The result of analysis showed that the risk of garlic farming was high. Most of farmers were ever behavior toward risk and the garlic farming inefficient. To develop the garlic farming more investment, input subsidy, and on time planting were required.